‘Teaching wellbeing’ in secondary schools in the 2020s: a qualitative interview and focus group project with secondary school teachers in England - Wilson, Rosanna (2025)
The state of mental health and wellbeing for young people and their teachers has been a rising concern in recent decades. Across OECD countries, there has been an increased focus on wellbeing in schools within policy and practice. Teachers are at the frontline of these issues. In 2020, the covid-19 pandemic arose, adding further complexity. In England, the teaching profession was required to absorb new policy requirements and “teach” wellbeing. Scant research existed to explore the practice implications for teachers as increased emphasis on wellbeing expectations emerged.